Wandel ostdeutscher Familiengedächtnisse : Erinnerungen der „Vertreibung“ zwischen Nationalsozialismus, Wende und Gegenwart - Meyer, Katinka (Soziales Gedächtnis, Erinnern und Vergessen – Memory Studies, 2020)
In a study of biography and memory theory, Katinka Meyer investigates the question of how East German families remember the "expulsion" of Germans from the former eastern regions. As a result of their settlement in the Soviet Zone / GDR, these families were confronted with an anti-fascist culture of remembrance. The study empirically reconstructs the complex interplay of internal family dynamics and social system changes - from National Socialism to the GDR to the Federal Republic - within the family memory. At the individual, intergenerational and family biographical level, it makes it clear that family history can be used to deal with traumas, to remember losses and to conceal Nazi perpetrators